Implementasi Standar Akuntansi Pemerintahan dan Kualitas Laporan Keuangan - Khadijah Darwin; Haliah Haliah; Nirwana Nirwana; Syamsuddin Syamsuddin; Andi Kusumawati (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
This study examines the impact of governmental accounting regulations on financial statement quality at BPKAD Buru, Indonesia. Using quantitative methods, data were collected via questionnaires from leaders and employees involved with BPKAD Buru. The sample size was (mention the sample size). Simple regression analysis revealed a significant positive correlation between adherence to governmental accounting standards and the quality of financial reports. Specifically, the findings indicate that (provide specific statistical findings, e.g., coefficients, p-values). Adherence to standardized accounting practices enhances financial report quality, with approximately 35.1% of the variance in regional financial reporting quality attributable to these standards. This underscores the crucial role of regulatory frameworks in improving financial transparency and accountability within governmental entities. This research contributes to public sector accounting discourse by elucidating the relationship between accounting regulations and financial reporting quality, offering valuable insights for policymakers, practitioners, and scholars focused on effective financial management and governance.